2014
DOI: 10.1111/ppa.12262
|View full text |Cite
|
Sign up to set email alerts
|

Differential defence responses of susceptible and resistant kimchi cabbage cultivars to anthracnose, black spot and black rot diseases

Abstract: The resistance of 27 commercial kimchi cabbage cultivars against Colletotrichum higginsianum causing anthracnose was evaluated. Among the cultivars with different disease severity, three cultivars, CR‐Hagwang, CR‐Hwangrock and Houseking‐125, showed moderate resistance. Two cultivars, Buram‐3‐ho (susceptible) and CR‐Hagwang (moderate resistance), were chosen for further investigation. Severe necrotic lesions were observed on the C. higginsianum‐inoculated leaves in cv. Buram‐3‐ho, whereas only a few scattered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…We suggested that the resistant cv. CR-Hagwang might activate SA, JA and ethylene-mediated defenses all together to combat pathogens having different infection strategies and to achieve broad spectrum disease resistance in our previous study ( Lee and Hong, 2014 ). Although SA application more or less reduced disease resistance to C. higginsianum and A. brassicicola in the susceptible cultivar, it did not occur in the resistant cultivar.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…We suggested that the resistant cv. CR-Hagwang might activate SA, JA and ethylene-mediated defenses all together to combat pathogens having different infection strategies and to achieve broad spectrum disease resistance in our previous study ( Lee and Hong, 2014 ). Although SA application more or less reduced disease resistance to C. higginsianum and A. brassicicola in the susceptible cultivar, it did not occur in the resistant cultivar.…”
mentioning
confidence: 86%
“…In our previous study, two cultivars of kimchi cabbage ( Brassica rapa var. glabra Regel) seedlings demonstrated differential disease resistance to infections by the hemibiotrophic fungus C. higginsianum, the necrotrophic A. brassicicola and the hemibiotrophic bacterium Xcc ( Lee and Hong, 2014 ). PR gene expressions were much more induced in the resistant cultivar CR-Hagwang treated with SA compared to the susceptible cultivar Buram-3-ho.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Alternaria spp. cause leaf spot that affects the quality of the products and can become a major problem during storage (Lee and Hong, 2015). Most of the important economic Brassica crops are hosts of A. brassicae (Table 1).…”
Section: Introductionmentioning
confidence: 99%